The Action Mode of Lysophosphatidylcholine in Human Monocytes - Mi-Ran Yun; Fumikazu Okajima; Dong-Soon Im (Elsevier, 2004)
To elucidate the action and signal transduction of lysophosphatidylcholine (LPC), we challenged a set of LPC on U937 human monocytes and found that LPC mobilized Ca2+. The Ca2+ response was not blocked by pertussis toxin, an inhibitor of Gi/o proteins, or by U73122, a phospholipase C inhibitor. Furthermore, the response was totally blocked by addition of EGTA to the extracellular media, suggesting that Ca2+ influx across the plasma membrane was the only source of LPC-induced Ca2+ response in the U937 cells. 16:0 and 18:0 LPC induced similar responses. Recently it has been suggested that two G protein-coupled receptors function as LPC receptors in the plasma membrane. RT-PCR analysis indicated that neither the G2A receptor nor the GPR4 receptor is expressed in the U937 monocytes. Our data suggests that another action mechanism of LPC may be involved in the LPC response in the U937 cells. Keywords:: lysophosphatidylcholine, atherosclerosis, G protein-coupled receptor, calcium influx, signal transduction